Psychosocial aspect and medical co-morbidity in Foster Care Children in Assiut Governorate - Hosny M.A. El-Masry; Islam S. Mohammed; Fatma A.A. El Saboor; Mohammed A. Aladawy; Hossam A.G. El Sayed Atta (Al-Azhar Assiut Medical Journal)
Background and aim Childhood is a developmental stage in which the importance of reciprocal emotional bonding between a child and his/her caregivers for healthy physical, psychological, and social development has been known for centuries. The Ministry of Social Solidarity regulates Foster care in Egypt according to detailed procedures of the child law No. 126 for 1996 and its amendments of 2008. We aimed to assess psychosocial aspects and medical co-morbidities in foster care children in the Assiut governorate and compare psychosocial problems and medical co-morbidities between foster care children and school children in the Assiut governorate. Patients and methods We compared a cross–sectional observational study psychosocial problems and medical co-morbidity in 50 children aged from 5 to 18 years old from September 1, 2018 to September 30, 2022 selected from Assiut governorate foster care centres to 50 healthy children from Assiut governorate schools matched for age and sex. Results There is a significant increase in attention problems, aggressive behavior, conduct disorder, bullying behavior, and attention-deficit hyperactivity disorder, depression, in foster care children. No difference in the prevalence of medical conditions between the two groups. Conclusion Children living in foster care are more prone to suffer from various mental health problems which are more prevalent in foster care children than other populations.